PRELIMINARY INVESTIGATION ON ANTIPYRETIC ACTIVITY OF CUSCUTA REFLEXA IN RATS - Bodhisattva Roy; Sanjib Bhattacharya (Journal of Advanced Pharmaceutical Technology & Research, 2010)
In present study, the antipyretic activity of aqueous and ethanol extracts fromCuscuta reflexa Roxb. (Cuscutaceae) was evaluated using Brewer’s yeast inducedpyrexia in rats. Both the extracts at 200 and 400 mg/kg body weight dose significantly (p< 0.05) reduced the increased rectal temperature. The extracts started reducing theelevated rectal temperature after 3 h of treatment in a dose related manner. At the dose of400 mg/kg body weight the aqueous and ethanol extract reduced 79 % and 83.8 %respectively of the elevated rectal temperature as compared to reference drug paracetamol(96.5 %) after 6 h of treatment. It was therefore concluded that both the extracts of C.reflexa demonstrated antipyretic activity, the ethanol extract was found to be slightlypotent than the aqueous extract.